(untitled) (Global Journal of Computer Science and Technology, 2022)
Abstract The idea of the Metaverse as a next iteration of the internet gets increasing attention As the development is still in its infancy maturity assessments of the Metaverse in general and of its constituting virtual worlds could provide important input to guiding research and development as well as investments Based on a scientific definition of the Metaverse eight core attributes for its virtual worlds are extracted For each of these attributes five maturity levels are defined Thus a Metaverse maturity model with eight attributes and five maturity levels is proposed